Protocol for prevention of pressure ulcer - Stuque, Alyne Gonçalves; Sasaki, Vanessa Damiana Menis; Teles, André Aparecido da Silva; Santana, Mary Elizabeth de; Rabeh, Soraia Assad Nasbine; Sonobe, Helena Megumi (Rev Rene, 2017)
Objective: to analyze the national and international scientific evidence to establish recommendations in the elaboration of a nursing protocol for the prevention of pressure ulcer. Methods: integrative review with search in the databases LILACS, MEDLINE and BDENF, using the descriptors “pressure ulcer”, “protocol” and “secondary prevention”, with final sample of 21 scientific articles. Results: the sample was categorized into two themes: “Protocols”, which recommends sociodemographic and clinical specificities with adoption of instrument and scales to measure skin and pressure ulcer lesions, in addition to nursing interventions; and “Strategies for implementing the protocol”, which emphasizes the leadership of nurses, management support, continuing education, prediction and provision of human and material resources as fundamental for the implementation. Conclusion: in the elaboration of a protocol for prevention of pressure ulcer, clinical and therapeutic aspects of the patients should be included, as well as material and human resources for its implementation.